Energy absorption performance of press-formed shell - Zubair, Khalil (2016)
Automobile body usually comprises many sheet metal components. Most of them are usually fabricated by various press-forming operations from sheet metal. The body designers will consider not only the strength for durability but also the structural ability to protect the occupants during impact in a collision event. Sheet metal components are collapsible and this plays an important role as the shock absorber of the kinetic energy exploit plastic deformation. Shape and material of each part and the loading condition, etc. affect the deformation behavior at collision. Thus the main objective of this thesis is to obtain the basic information in constructing the guidelines when designing energy absOrber.This is done by studying several simple conditions in energy absorbing deformation behavior. In the thesis, two kinds of dome shaped shells made by press-forming were deformed by indentation of the simple shaped indentors. Effects on the shell shape, height and the indentor shape in the deformation behavior were then investigated. The objective is to show the fundamental effective information for crashworthy design of press-formed sheet metal parts. The dome shaped specimen was flat-top or hemispherical axisymmetric shell. This was produced by press-forming operation using a circular blank of aluminum alloy A5052. The head shape of the indentor was flat or hemispherical. Numerical simulation was also conducted to predict the deformation patterns and the forces in the press-forming and the indentation using the dynamic explicit finite element code DYNA313 (Public domain version). The energy absorption performance of the shell was evaluated as the consumed energy by the deformation where the indentor travelled up to the length equal to the shell height. The most effective deformation condition for such performance was obtained in the deformation of flat-top shell by flat-headed indentor. Rising tendency in indentation force was duller, when the hemispherical-headed indentor was applied, in contrast to the case where a flat-headed indentor was used. A peculiar crushing load characteristic was observed, when the load was increased, and then decreased for the combination of hemispherical shell and flat-headed indentor. Plastic buckling occurred due to the radial compressive stress upon the material contact to the flat part of the indentor. These phenomena were successfully reproduced in the numerical simulation. Further, when the Bauschinger effect of the material was appropriately introduced into the numerical simulation, the indentation force became closer to the experimental result. In addition, experiment was also conducted on mild steel SPCE sheets using flat or hemispherical headed indentor under impact condition using a drop hammer or quasi-static one. As a result, several characteristic force variations appeared. Almost flat indentation force is available in the combination of hemispherical shell and round headed indentor. The in-plane compressive stress field in the material induces the increase in indentation force, which in turn increases the energy absorption capacity. The force in impact test of SPCE was approximately 1 .5 times higher than that in quasi-static test. The experimental results obtained here implies that the strain-rate effect on the stress tends to be enhanced if the loading direction alters. On the other hand,whe nI we compard the results to aluminium alloy A5052-1134, it did not show the same tendency as SPCE. Aluminum alloy A5052-H34 and mild steel SPCE have comparable performance in energy absorption under impact in the range of the present experiments.' . The positive strain-rate effect f SPCE under the reverse in 5. loading direction may improve the performance When comparing the energy absorption performance uhder impact for the 10 mm diameter indentor with the 30 mmone, the energy absorption performance of 10 mm indentor is around 20 % larger. The reason was because the concentrated indentation force by the indentor caused severe bending to the shell's wall, thus increasing the load to a higher level within the fracture limit of the shell height. In the present study, several basic characteristics in the indentation behavior were revealed for the simple collapse conditions, thus providing some helpful guidelines in designing the collapsible parts and structures.